PERAN KNOWLEDGE SHARING DALAM PENYELESAIAN KONFLIK DI PERUSAHAAN - Dede Mustomi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2020)
Sharing knowledge or knowledge sharing has become a separate culture within the company, especially in conflict management. Conflict will always exist as long as two or more humans interact. The difference lies in the size of the conflict. The smaller the conflict, the easier and faster it will be resolved. There are many ways to resolve conflicts, one of which is by implementing or cultivating knowledge sharing within the company. Knowledge sharing makes companies have a breath of togetherness. Every employee who closes himself to one another and is individualistic in the end will eventually create a conflict. This study is to find answers to how the role of knowledge sharing in conflict resolution. This research is a descriptive study using a survey method of 90 respondents. There are 10 questionnaire questions that are given to respondents asking for yes or no answers to each question. The result, of the 10 questions, there were 2 questions where the respondent chose all of the answers yes, while for other questions the respondents were divided, some answered yes and some answered no. The third survey question is the question with the highest standard deviation with a number of 0.461, which means that the data distribution is the most varied.